A feasibility study of activity tracking devices in pregnancy - Michelle A. Kominiarek; Lauren C. Balmert; Hallie Tolo; William Grobman; Melissa Simon (BMC, 2019)
Abstract Background We aimed to evaluate the feasibility of using an activity-tracking device (ATD) during pregnancy and compare self-reported to ATD-calculated energy expenditure in a 2-phase study. Methods (Phase 1) Twenty-five pregnant women were asked about exercise, computer use, smartphone ownership, and ATD attitudes. Descriptive statistics were reported. (Phase 2) Women ≥18 years, smartphone owners, < 16-weeks gestation, and without exercise restrictions were approached to participate in 2016-2017. Women received instructions to wear and sync the ATD daily. We assessed protocol adherence and satisfaction via surveys at 36-weeks and used mixed models to assess the relationship between gestational age and ATD data. Energy expenditure from the Pregnancy Physical Activity Questionnaire (PPAQ) was compared to ATD-calculated energy expenditure. Results (Phase 1) Walking was the most common exercise; 8% did not perform any activity during pregnancy. All women had internet access and owned a smartphone. Women stated they would wear the ATD all the time during a pregnancy (88%), with the intent to improve their health (80%). (Phase 2) The characteristics of the 48 women were: pre-pregnancy BMI 28, 62% non-Hispanic black, 62% multiparas. Of the 18 women who completed the 36-week survey, only 56% wore the ATD daily, 33% had a lost or broken ATD, and 17% had technical problems; however, 94% enjoyed wearing it, 94% would recommend it to a pregnant friend, and 78% thought it helped them reach activity goals. According to ATD data, the median number of active days was 41 (IQR 20-73) and the median proportion of active days out of potential days was 22% (IQR 11-40). As gestational age increased, mean log steps decreased, active minutes decreased, and sedentary hours increased in unadjusted and adjusted models (P < 0.05 all comparisons). There were no differences in mean energy expenditure (MET-h/week) estimated by PPAQ or ATD data at 28 weeks gestation [212 (22-992 range) vs. 234 (200-281 range), P = 0.66] and at 36 weeks [233 (86-907 range) vs. 218 (151-273 range), P = 0.68]). Conclusions Women reported high motivation to wear an ATD and high satisfaction with actually using an ATD during pregnancy; however adherence to the study protocol was lower than expected and ATD technical problems were frequent.